Implementation: a framework for facilitating employee adaption to major organizational transitions - Marks, Mitchell Lee (Henry Stewart Talks, 2014)
10 realities about organizational transition and employee adaptation, Implications for action, Requirements & levels for facilitating adaptation, Four elements for facilitating adaptation (Empathy, Engagement, Energy, Enforcement), Case example for action during a transition